Paper Summary: Probabilistic Planning for Continuous Dynamic Systems under Bounded Risk - Ono, Masahiro; Williams, Brian; Blackmore, Lars (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
This paper presents a model-based planner called the Probabilistic Sulu Planner or the p-Sulu Planner, which controls stochastic systems in a goal directed manner within user-specified risk bounds. We first develop a new plan representation called a chance-constrained qualitative state plan (CCQSP), through which users can specify the desired evolution of the plant state as well as the acceptable level of risk. We then develop the p-Sulu Planner, which can tractably solve a CCQSP planning problem.